BANGKITAN PERJALANAN RUMAH TANGGA DI KECAMATAN DARUSSALAM KABUPATEN ACEH BESAR - Sufri Helmi; Noer Fadhly; Yusria Darma (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Darussalam Sub-district is one of the largest sub-districts consisting 29 villages in Aceh Besar Regency. This sub-district serves its function for settlements, offices, trading, and education. As there are many people reside in the area, the trip-generation and traffic rate to the activities centers also increase and it requires adequate road capacity. Therefore, a trip-generation model is to estimate the number of people who travel needed in Darussalam area. This study aims to define the trip-generation pattern from and to home based on the level of education and type of occupation concerning the mandatory activities. Moreover, it aims to determine the vehicles proportion used by the people in the mandatory activities. The sampling technique used in this research is proportionate stratified random sampling. The result of this study shows that factors that influencing trip-generation of people with the education level under High School at the mandatory time are actually the age. While for people with the education background above the high school level, their trip-generation depends on the family structure, the number of family members in the family working, the number of motorcycles in the family, and the number of the family owning the driving license. Moreover, the factors influencing the trip-generation of people who do not work for government at the mandatory activities are age, the number of family members who work, and the number of family members who are still students. At the other hand, the factors influencing the trip-generation of people who work for the government at their mandatory activities are the number of motorcycles in the family, the number of cars in the family, and the number of family members owning driver license. The dominant modes of transport used by the residents of Darussalam Sub-district at all education and working travels for mandatory activities are motorcycles which are 218 modes (72.6%) and cars which are 82 modes (217.33%).